Revisiting Risk Governance of GM Plants: The Need to Consider New and Emerging Gene-Editing Techniques - Agapito-Tenfen, Sarah Z.; Okoli, Arinze S.; Bernstein, Michael J.; Wikmark, Odd-Gunnar; Myhr, Anne I. (Frontiers in Plant Science, 2018)
New and emerging gene-editing techniques make it possible to target specific genes in the genome of species with greater speed and specificity than previously possible. Of major relevance for plant breeding, regulators and scientists are discussing how to regulate products developed using these gene-editing techniques. Such discussions include whether to adopt or adapt the current framework for GMO risk governance in evaluating the impacts of gene-edited plants, and derived products, on the environment, human and animal health. Product classification or definition is one of several aspects of the framework being criticised. Further, knowledge gaps—for example related to target and off-target effects of intervention in plant genomes—related to risk assessments of gene-edited organisms developed with new and emerging gene-editing techniques are also of concern. Resolving these and related aspects with the current framework will involve addressing many subjective, value-laden positions, for example how to specify protection goals through ecosystem service approaches. A process informed by responsible research and innovation practices, involving a broader community of people, organizations, experts, and interest groups, could help scientists, regulators, and other stakeholders address these complex, value-laden concerns related to gene-editing of plants with and for society.